(untitled) (Research, Society and Development, 2022)
Polyunsaturated fatty acids (PUFAs) are essential for human functions and can be used in nutraceuticals; however, traditional sources are environmentally unsustainable. A promising strategy to reduce the production costs of PUFAs is the use of economical agro-industrial sources as substrates in culture media for oleaginous microorganisms. In this study, we investigated the potential of the fungus Lichtheimia hyalospora UCP 1266 (isolated from the Caatinga soil, Brazil) in the production of PUFAs, through the metabolic conversion of alternative substrates crude glycerol (CG) and corn steep liquor (CSL). The cultivation of L. hyalospora UCP 1266 in medium containing glucose (Synthetic Medium for Mucorales - SMM) yielded 2.1 g/L of biomass and 0.6 g/L of total lipids. However, assay 4 of the 22 full-factorial design, with CG 8% and CSL 8%, provided higher yields of biomass (15.5 g/L) and total lipids (12.8 g/L). The lipids produced in this medium presented a composition of saturated, monounsaturated and polyunsaturated fatty acids (SFAs=35.13%, MUFAs=46.09% and PUFAs=18.14%). The microorganism proved to be promising in the production of omega 6 (linoleic acid, C18:2), γ-linolenic acid (C18:3), omega 3 (α-linolenic acid, C18:3) and omega 9 (oleic acid, C18:1). The results indicated L. hyalospora UCP 1266 as an oleaginous fungus with great potential for use in the development of nutraceutical ingredients for food or applied in cosmeceuticals and/or nutricosmetics.